Governance in Crisis. Examining the Role of TSOs in Asylum Seekers Reception in France and Italy - Trasciani Giorgia (Nonprofit Policy Forum)
Although third sector organizations (TSOs) played a vital role in supporting public authorities during the European migration crisis, their involvement in governance structures remains underexplored. This paper examines the evolving relationships between TSOs and public authorities in this sector, focussing on the governance shifts triggered by the crisis. By comparing Italy and France – two countries with distinct roles and responses – the study reveals a convergence in their crisis management strategies and the resulting impact on TSOs. Despite initial differences, both nations experienced a marketization of relations, transforming service provision and governance models. This paper analyzes the mechanisms regulating the crisis and their effects on the roles and interactions of key actors. The comparative analysis underscores a broader trend toward the normalization of crisis response systems, providing critical insights into the future of governance models in migration management.